Effectiveness of ketofol versus propofol induction on hemodynamic stability in adult elective surgery - Abdulahi, Hamed; Shamsi, Afzal; Vahedi, Saeid; Mghames, Husam Kareem; abdulhasan, Afaf (Journal of Neonatal Surgery, 2025)
Introduction: A serious side effect of anaesthesia is haemodynamic instability, which can be brought via induction, intubation, surgical wounds other stress, hypovolemia, anaesthesia medications, even volatile anaesthetics. Pain from the surgical incision raises your pulse & arterial pressure. Individuals with ischaemic heart disease, valvular heart disease, and various other cardiovascular conditions have this difficulty more frequently. Blood pressure is sharply lowered by medications used to induce anaesthesia. Through a number of methods, propofol lowers blood pressure, whereas ketamine raises it and vice versa. [1]. Propofol & ketamine are frequently used as induction agents for adult surgical patients in the operative room; however, cardio respiratory depression may caused during the induction of anesthesia by the propofol drug, while raises arterial blood pressure and heart rate may caused by ketamine. However, it appears that ketamine and propofol have complementing clinical effects. One of the most common drug used frequently for procedural sedation is the ketofol drug , it will be crucial to investigate its efficacy for induction in order to provide surgical patients with clinical care [2]. Method and Materials: This study's primary goal aimed to examine the hemodynamic impacts of propofol drug with ketofol drug during the elective surgery patients within fifteen minutes after general anesthesia induction. The research was conducted among 92 patient divided in two groups propofol and ketofol group who using the standard procedure of general anesthesia in Baghdad teaching hospital in Baghdad City. Study participants will be selected from all patients who have inclusion criteria using Convenience Sampling from November 2024 in Baghdad teaching hospital. Inclusion criteria: All patients who was ASA I and ASA II and the patient was between the ages of 18 to 65 all these patient met the inclusion criteria who utilized from general anaesthesia during the elective surgery. Exclusion criteria: Patients who had undergone ENT surgery, neurosurgery, long-term opioid usage, sedative preoperative adjunctive medicines, psychiatric drug use, known ketamine or propofol allergies, or were in discomfort were not included. Findings: in our study we found the Mean standard deviation of the age of the ketofol group was (38.41 12.54). the Mean standard deviation for age of propofol group was (40.16 12.60) . (63%) of ketofol group were male . (67.4% ) of propofol group were male. The Mean standard deviation of the weight of ketofol group was(74.15 8.64) . The Mean standard deviation of the weight of the propofol group was (75.24 9.63).( 91.3%/) of the ketofol group were ASA1. (92.4%)of the propofol group were ASA1. the Mean standard deviation of the SBP of ketofol group immediately after injection was (129.63 6.45) and for the propofol group was (125.25 13.25) and the p-value was (0.006) there is significant results between the two groups. The Mean standard deviation of the MAP of ketofol group was (94.78 8.69) and for the propofol group was (87.14 8.33) and the p-value was (0.000) there is statically differences between the two groups. also, the Mean standard deviation of the SBP of ketofol group immediately after injection was (129.63 6.45) and for the propofol group was (125.25 13.25) and the p-value was (0.006) there is significant results between the two groups. also, the Mean standard deviation of the SBP of the ketofol group immediately after injection was (126.01 8.48) and for the propofol group was (120.39 11.33) and the p-value was (0.003) there is significant results between the two groups of propofol group with ketofol group in this finding. Conclusion: The findings from our research results lead us to the conclusion which, for the first ten minutes, for better hemodynamic stability during the general anesthesia we used the ketofol drug and it has better stability than using propofol drug. The groups did not vary in terms of postoperative pain or PONV